Longitudinal diffusion tensor imaging in Huntington's Disease - Weaver, Kurt E.; Richards, Todd L.; Liang, Olivia; Laurino, Mercy Y.; Samii, Ali; Aylward, Elizabeth H. (Experimental neurology, 2009)
Serial diffusion tensor imaging scans were collected at baseline and 1 year follow-up to investigate the neurodegenerative profile of white matter (WM) in seven individuals with the Huntington's Disease (HD) gene mutation and seven control subjects matched on age and gender. In the HD subjects, but not controls, a significant reduction of fractional anisotropy (FA), a measure of WM integrity, between baseline and follow-up was evident throughout the brain. In addition, a DTI scalar associated with the stability of axons, axial diffusivity, showed significant longitudinal decreases from year 1 to year 2 in HD subjects, declines that overlapped to greater degree with FA discrepancies than longitudinal increases in radial diffusivity, a DTI variable sensitive to demylinization. These preliminary results provide the first longitudinal DTI evidence of WM degeneration in HD and support the notion that FA abnormalities in HD may be a result of axonal injury or withdrawal. These results suggest that longitudinal FA changes may serve as a neuropathological biomarker in HD.